2021
DOI: 10.3390/jcm10081645
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Colonization as a Possible Source of Overactive Bladder Symptoms in Pediatric Patients: A Literature Review

Abstract: Overactive Bladder (OAB) is a common condition that is known to have a significant impact on daily activities and quality of life. The pathophysiology of OAB is not completely understood. One of the new hypothetical causative factors of OAB is dysbiosis of an individual urinary microbiome. The major aim of the present review was to identify data supporting the role of bacterial colonization in overactive bladder symptoms in children and adolescents. The second aim of our study was to identify the major gaps in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…(1) UTI: Since the establishment of the standard urine culture in the 1950s until approximately 10 years ago, the UT had been considered sterile under normal conditions [7][8][9][10][11]. This perspective is now altered with the discovery of the genitourinary microbiome and the demonstration that most urinary bacteria identified by 16S sequencing can be cultured under expanded conditions [10,12]. As symptomatic UTI is the outcome of an altered UM makeup, some researchers have suggested that the terms "UTI" and "asymptomatic bacteriuria" be replaced by the term "dysbiosis" [14].…”
Section: Limitation Of Microorganism Detection Methods and Their Inte...mentioning
confidence: 99%
See 3 more Smart Citations
“…(1) UTI: Since the establishment of the standard urine culture in the 1950s until approximately 10 years ago, the UT had been considered sterile under normal conditions [7][8][9][10][11]. This perspective is now altered with the discovery of the genitourinary microbiome and the demonstration that most urinary bacteria identified by 16S sequencing can be cultured under expanded conditions [10,12]. As symptomatic UTI is the outcome of an altered UM makeup, some researchers have suggested that the terms "UTI" and "asymptomatic bacteriuria" be replaced by the term "dysbiosis" [14].…”
Section: Limitation Of Microorganism Detection Methods and Their Inte...mentioning
confidence: 99%
“…(2) UUI and OAB: OAB is a poorly understood disorder, but is thought to be multifactorial and is believed to originate from abnormal neuromuscular signaling and functioning of the detrusor muscle [10,22]. In the pediatric population, OAB not only burdens the child's development but also negatively impacts the family [12]. OAB is a condition where frequent urination is required, which often leads to UUI.…”
Section: Limitation Of Microorganism Detection Methods and Their Inte...mentioning
confidence: 99%
See 2 more Smart Citations
“…Dysbiosis of the urobiome has been related to an increased risk of urinary tract infection, nephrolithiasis, and dysfunction of the lower urinary tract [ 9 , 10 , 33 ]. Although most studies focused on adults, the number of investigations evaluating the relationship between the urobiome, dysbiosis, and urinary tract diseases in children increases [ 11 , 24 , 34 , 35 ].…”
Section: Dysbiosis and Urinary Tract Infectionmentioning
confidence: 99%